S.O.S professor inclusivo: reflexões e contribuições para apoiar a prática docente voltada aos alunos com deficiência visual na disciplina de ciências naturais - BORGES FILHO, Edmar Fernandes (Universidade Federal do Pará, 2020)
The present research was based on the legal bases of Special and Inclusive Education that orient the teaching practices in Brazil, focusing on the reality about the formation of Natural Sciences teachers within an inclusive perspective for People with Visual Impairment (PcDVs). The objective of this work was to systematize a site that supports the continuing education of Natural Sciences teachers in the inclusion of PcDVs, adding values of the educational trends of Science Teaching. Taking as a starting point, the present study followed the qualitative research of Ludke and André (1986). A priori was carried out a bibliographical analysis inside a repository site of scientific productions, soon it was evaluated the quantitative of research on Science Teaching within an inclusive perspective in the last 20 years. Subsequently, a documentary analysis of the Pedagogical Political Projects of the Full Degree courses in Natural Sciences of the State and Federal Universities, both of the state of Pará, was carried out, with the purpose of investigating and evaluating the curricular proposals in the formation of professors before the demands Inclusive Education. In addition to this study, an exploratory research was conducted based on in-depth interviews with educators working in the aforementioned public universities, as well as graduates of the undergraduate degrees in them. It was verified that Inclusive Education is a little present reality along the formation of Natural Sciences teachers, allowing the emergence of many pedagogical barriers that limit the inclusion within a classroom. In view of this perception, it was observed the need for an attention to the process of continuous training of Natural Science educators, considering the didactic-pedagogical orientation for the improvement of Science Teaching. To this end, the development of a website accessible on the smartphone platform has become relevant in order to make Inclusive Education theory applicable to Science Teaching, thus allowing the teacher to innovate methods and resources in order to develop appropriate solutions to achieve a process of egalitarian and inclusive teaching and learning. The first version of the site was validated by an expert panel composed of Natural Sciences teachers, the results were positive, pointing out that users had good experiences using the tools available on the site. Given the feedback of the experts' evaluation, it allowed specific adaptations in the site and consequently allowed to aggregate knowledge to the user in order to provide a more satisfactory experience. Thus, it is concluded that this research, despite not having an institutional financing, associated with the absence of professionals specialized in the area of website programming, has brought innovative proposals and significant investments, both for Science Teaching and Inclusive Education.